Hubungan Pemanfaatan Media Youtube dan Kepercayaan Diri Siswa Sekolah Dasar (SD) Dalam Menyelesaikan Soal Matematika - Muhammad Zaid (STKIP Andi Matappa Pangkep, 2024)
This study aims to determine the relationship between the use of YouTube media and self-confidence together with the results of solving mathematics problems. Students' self-confidence plays an important role in building confidence in their ability to understand concepts and solve problems. YouTube learning media provides access to interactive, visual, and easy-to-understand explanatory videos. The type of research used is quantitative with survey methods and correlational techniques. Data collection used is the YouTube media utilization instrument and self-confidence in the form of a closed questionnaire with a Likert scale and a mathematics problem solving instrument. The data analysis technique used is the prerequisite test and simultaneous test (F test). The population in this study was 138 students of SDN 3 Sambung Jawa. The sample used was 30 grade V students. The results of the study showed that there was a partial relationship between the use of YouTube media and self-confidence with the results of solving mathematics problems.